Tutorials in metamaterials - Noginov, Mikhail A.; Podolskiy, Viktor A. (Series in nano-optics and nanophotonics., 2012)
"From science fiction to science laboratoriesDiscover the State of the Art in Photonic MetamaterialsMetamaterialsomposite media with unusual optical propertieshave revolutionized the landscape of optical science and engineering over the past decades. Metamaterials have transformed science-fiction-like concepts of superresolution imaging and optical cloaking to the realm of science laboratories, and further promise to transform these into the realm of our everyday life. This new era of optical metamaterials calls for the development of experimental and theoretical methods capable of analyzing optical behavior on the multitude of scalesfrom the nanometer scale of individual inhomogeneity, to the micrometer level and the larger scale of metamaterials-based devices. Tutorials in Metamaterials offers a collection of chapters that were designed as self-contained tutorials describing photonic metamaterials and the state of the art in metamaterials research. Chapters cover:Linear and nonlinear properties of photonic metamaterials and their potential applicationsFabrication techniques for optical metamaterials, ranging from electron-beam lithography, focused ion beam milling, and nanoimprint lithography to direct laser writingRecent achievements in metatamerial research at visible, IR, and microwave frequenciesNovel applications of metamaterials for light guiding, steering, and refractionEfforts to compensate and eliminate optical loss by introducing optical gain into the metamaterial matrixA comprehensive overview of metamaterial photonics, this reference is suitable for graduate students as well as physicists and engineers interested in entering this dynamic new field"--